Electrical transport in thin films of glassy Ge₄₀Te₆₀-xSbx alloys - Shukla, S.; Kumar, S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Glassy alloys of Ge₄₀Te₆₀-xSbx (where x = 2, 4, 6 and 10) were prepared by conventional rapid melt-quenching technique. The nature of the alloys was ascertained through X-ray diffraction pattern of the samples. Thin films of the aforesaid materials could be prepared over the glass substrate by thermal evaporation technique. Vacuum evaporated indium electrodes were used here to perform electrical measurements. Coplanar structure of thin films was used in this case. The dc electrical conductivity measurements have been carried out. The dark conductivity, pre-exponential factor and activation energy have been calculated for various compositions. It has been found that the dark conductivity and pre-exponential factor increase, while the activation energy decreases with Sb concentration in Ge₄₀Te₆₀-xSbx system. The results can be reserved as an evidence for the chalcogenide nature defects in the above material.